The Diverse Implementation of Geriatrics‐Orthopedics Comanagement Programs in the United States. Issue 8 (6th July 2020) - Rogers, Stephanie E.; Ko, Jocelyn S.; McNicoll, Lynn; Mendelson, Daniel Ari
Abstract : BACKGROUND: Many health systems are establishing geriatrics‐orthopedics (Geri‐Ortho) comanagement programs; however, there is paucity of published information on existing programs' variations in clinical operations, structure, and reported implementation challenges and perceived successes. OBJECTIVE: Our objective was to obtain detailed information about the variety of existing Geri‐Ortho comanagement programs in the United States. DESIGN/PARTICPANTS: We conducted a cross‐sectional survey of 44 existing Geri‐Ortho comanagement programs, with 23 (52%) of programs responding. MEASUREMENT: Quantitative questions were used to assess operational, staffing, and financial structures; and qualitative questions were used to identify reported challenges and perceived successes of implementation. RESULTS: Programs self‐identified as urban (n = 23), academic (n = 20), or nonprofit (n = 22) and as having a level I trauma center (n = 17). Most programs (n = 18) were funded fully by the institution. Fourteen programs used geriatricians, and nine used medicine/hospitalists as the supporting clinical service, whereas approximately half (n = 11) used these services in a true comanagement model. Six universal themes were identified as necessary for program implementation. The most commonly described successes perceived by all respondents were improvements in clinical outcomes and better interdisciplinary relationships. Reported challenges included difficulty in interdisciplinary geriatrics education, difficulty in adherence to protocols, and lack of funding for staffing. CONCLUSIONS: There are diverse types of Geri‐Ortho comanagement programs in the United States, although universal elements exist. Many had similar challenges in implementation, and further studies are needed to determine which implementation elements are critical to clinical and financial outcomes. J Am Geriatr Soc 68:1714‐1719, 2020.